PCR-RFLP Using BseDI Enzyme for Pork Authentication in Sausage and Nugget Products - Y Erwanto; M Z Abidin; A Rohman; . Sismindari (Media Peternakan, 2011)
A polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) using BseDI restriction enzyme had been applied for  identifying the presence of pork in processed meat (beef sausage and chicken nugget) including before and after frying. Pork sample in various levels (1%, 3%, 5%, 10%, and 25 %) was prepared in a mixture with beef and chicken meats and processed for sausage and nugget. The primers CYTb1 and CYTb2 were designed in the mitochondrial cytochrome b (cyt b) gene and PCR successfully amplified fragments of 359 bp. To distinguish existence of porcine species, the amplified PCR products of mitochondrial DNA were cut by BseDI restriction enzyme. The result showed pig mitochondrial DNA was cut into 131 and 228 bp fragments. The PCR-RFLP species identification assay yielded excellent results for identification of porcine species. It is a potentially reliable technique for pork detection in animal food processed products for Halal authentication.